2017
DOI: 10.2147/ott.s122908
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of patients with metachronous second primary lung adenocarcinomas

Abstract: BackgroundThe incidence of adenocarcinomas as multiple primary lung cancers (MPLCs) is increasing. How to determine the treatment strategies of MPLCs, especially second primary lung adenocarcinomas (SPLACs), and the prognostic factors associated with it are unclear.MethodsThe clinical records of patients undergoing surgery for second adenocarcinomas based on Martini–Melamed criteria between 2001 and 2014 were retrospectively reviewed. Survival rates were calculated by the Kaplan–Meier method and compared using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…Second, the SEER database did not include details on pulmonary function and associated medical comorbidities and surgical approaches (open or minimally invasive), which made it difficult to identify for further analysis the patients at high risk. However, we have noted that some previous studies did not report the prognostic significance of the pulmonary functions [8,9,28]. More studies and larger cohorts are needed to study the value of different operations for advanced diseases.…”
Section: Commentmentioning
confidence: 84%
See 1 more Smart Citation
“…Second, the SEER database did not include details on pulmonary function and associated medical comorbidities and surgical approaches (open or minimally invasive), which made it difficult to identify for further analysis the patients at high risk. However, we have noted that some previous studies did not report the prognostic significance of the pulmonary functions [8,9,28]. More studies and larger cohorts are needed to study the value of different operations for advanced diseases.…”
Section: Commentmentioning
confidence: 84%
“…Surgical type of the first cancer was not a significant prognostic factor in this cohort. As for lobectomy and sublobectomy in the first cancer treatment, Zhao and colleagues [28] found no significant prognostic difference between them for the first cancer. van Rens and colleagues [22] also did not report the different effect of lobectomy and limited resection for the first cancer on overall survival.…”
Section: Commentmentioning
confidence: 99%
“…6,7 Although surgical resection becomes necessary to prolong patients' survival, controversies related to diagnosis, patient selection, treatment, and outcomes still exist. 8 Although surgery offers the best chance for potential cure of MPLC and provides the most sufficient samples for diagnosis, 9 the prognosis of MPLC after surgery has not been studied in detail. In this study, the aim was to identify factors related to MPLC treatment outcomes, as well as the clinical features of affected patients, using the database of cases of surgically resected NSCLC cases in the year 2010 compiled by the JJCLCR.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported early and late outcomes in patients with multiple synchronous 5,9-13 or metachronous [14][15][16] lung cancers. These studies evaluated ipsilateral and contralateral multiple primary lung cancers, often considering data for both these situations, but few studies have specifically described outcomes following contralateral surgical resection.…”
Section: Discussionmentioning
confidence: 99%